Best Answer

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

Q: What is the factor of 3a plus ax plus 3b plus bx?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

a(x + y + z)

Ax + Bx + C is called an algebraic expression.

x2+bx+ax+ab = x2+ax+bx+ab = x(x+a)+b(x+a) = (x+a)(x+b)

Related questions

(x + 3)(a + b)

6a square plus b square

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

a(x + y + z)

ax + ay - AZ = a(x + y - z)

a(x + y - z)

Ax + Bx + C is called an algebraic expression.

x2+bx+ax+ab = x2+ax+bx+ab = x(x+a)+b(x+a) = (x+a)(x+b)

AX + BY is not an equation .AX + BY + C = 0is the general equation for a straight line.

ax + b = 15 or ax + b = -15

y = (c - Ax) / (B)